2021
DOI: 10.3390/w13223272
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Island Urbanization on Freshwater Lenses: A Case Study on a Small Coral Island

Abstract: Freshwater resources on small coral islands mainly exist in the form of freshwater lenses. The freshwater lens is highly vulnerable to salinization due to natural recharge variations and urbanization construction. However, it is unclear how a freshwater lens evolves under the influence of urbanization construction and which factors control its evolution. Based on the hydrogeological data of a small coral island in China, a corresponding 3D numerical model was established by the Visual MODFLOW software to inves… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 25 publications
0
3
0
Order By: Relevance
“…With no statistically significant difference between the analytical and numerical solutions, the results demonstrated that the lowest intensity situation resulted in the greatest pulling rate. The findings were consistent with previous research [26,27]. Finally, the study assessed the efficiency of the numerical chart and found that the execution of the program with a low n-value produced results that were just as accurate as those with a high n-value.…”
Section: Outcomes and Discussionsupporting
confidence: 90%
“…With no statistically significant difference between the analytical and numerical solutions, the results demonstrated that the lowest intensity situation resulted in the greatest pulling rate. The findings were consistent with previous research [26,27]. Finally, the study assessed the efficiency of the numerical chart and found that the execution of the program with a low n-value produced results that were just as accurate as those with a high n-value.…”
Section: Outcomes and Discussionsupporting
confidence: 90%
“… a Adapted from previous studies. ,, Boldfaced numbers with an underline are the reference values of L 2 , b 2 , and K 3 . …”
Section: Resultsmentioning
confidence: 99%
“…However, the numerical model is limited by field data, and the combination of various methods ignores the influence of tidal fluctuation which affects the vertical flow and the release or compression of water [24,25]. Ling et al (2021) used a three-dimensional numerical model of variable density flow and solute transport to study the impact of island urbanization on FGL on a small coral island in Sansha City, Hainan Province, China. However, it overlooks environmental factors such as tides and natural disasters [26].…”
Section: Introductionmentioning
confidence: 99%
“…Ling et al (2021) used a three-dimensional numerical model of variable density flow and solute transport to study the impact of island urbanization on FGL on a small coral island in Sansha City, Hainan Province, China. However, it overlooks environmental factors such as tides and natural disasters [26]. Zhang et al (2021) developed new analytical solutions for the steady-state heads and nondispersive SFI, which considered extended situations where reclaimed soils were more permeable than the original aquifer.…”
Section: Introductionmentioning
confidence: 99%